Chemical communication : chemical characterization of volatile constituents of urine of the southern African cheetah, Acinonyx jubatus jubatus, using headspace sampling and GC-MS - Visser, Runine (Runine Cecile) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2002.